REPRESENTASI KOLONISASI TERHADAP MASYARAKAT KULIT HITAM AFRIKA DALAM NOVEL THINGS FALL APART KARYA CHINUA ACHEBE - Hadiyanto, . (HUMANIKA, 2014)
Abstract This article discusses white-skinned race colonization and its impacts on African black-skinned race tribal society and culture in African Anglophone novel Things Fall Apart written by Chinua Achebe. The approach used in this research is post-colonial approach by using post-colonial theory to analyze phenomena as well as the implication of the colonizer and the colonized relationship. The result of this research indicates that the coming of white-skinned race colonialists in African Ibo tribe community with their colonization and cultural imperialism is implemented with varied strategies. Those strategies are proven effectively in strengthening white-skinned race’s colonial hegemony in Africa. The white-skinned race colonialists’ imperialism results in horizontal conflict and cultural-social disintegration in African native society; between the pro-colonial and the anti-colonial. Anti-colonial resistence is shown by most African native society to fight against colonial government arrogance and to resist white-skinned race imperialism in Africa. Keywords: African black-skinned race traditional culture, white-skinned race colonization, horizontal conflict, social-cultural disintegration